2021
DOI: 10.1002/jnr.24946
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in endocannabinoid signaling is associated with differential network‐level functional connectivity in youth

Abstract: The endocannabinoid system is an important regulator of emotional responses such as fear, and a number of studies have implicated endocannabinoid signaling in anxiety. The fatty acid amide hydrolase (FAAH) C385A polymorphism, which is associated with enhanced endocannabinoid signaling in the brain, has been identified across species as a potential protective factor from anxiety. In particular, adults with the variant FAAH 385A allele have greater fronto‐amygdala connectivity and lower anxiety symptoms. Whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…With respect to genetic factors of eCB signaling, a recent study reported that the fatty acid amide hydrolase (FAAH) C385A polymorphism was associated with this signaling in the brain [ 73 ]. Epigenetic modifications of the eCB may be related to DNA methylation or histone acetylation/deacetylation [ 73 ].…”
Section: The Association Between the Endocannabinoid Systems And Redo...mentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to genetic factors of eCB signaling, a recent study reported that the fatty acid amide hydrolase (FAAH) C385A polymorphism was associated with this signaling in the brain [ 73 ]. Epigenetic modifications of the eCB may be related to DNA methylation or histone acetylation/deacetylation [ 73 ].…”
Section: The Association Between the Endocannabinoid Systems And Redo...mentioning
confidence: 99%
“…With respect to genetic factors of eCB signaling, a recent study reported that the fatty acid amide hydrolase (FAAH) C385A polymorphism was associated with this signaling in the brain [ 73 ]. Epigenetic modifications of the eCB may be related to DNA methylation or histone acetylation/deacetylation [ 73 ]. Epigenetic modifications of the eCB may be related to DNA methylation and histone acetylation/deacetylation, and FAAH genes encoding the CB1 receptor and FAAH hydrolyzing enzyme play a relevant role in neurological disease pathogenesis and progression [ 73 ].…”
Section: The Association Between the Endocannabinoid Systems And Redo...mentioning
confidence: 99%
See 1 more Smart Citation
“… 131 Healthy male adults carrying AC heterozygotes have higher levels of AEA and lower anxiety scores than CC homozygotes, 132 and carriers of the A allele have been found to have more robust neural network connectivity and lower anxiety levels in adolescents. 133 Similarly, knock-in of the FAAH C385A gene in mice significantly ameliorated anxiety-like behavior, which was associated with reduced FAAH expression, elevated AEA levels, and enhanced eCB signaling. 134 However, additional studies have shown that the FAAH C385A genetic variant in children increased the risk of anxiety.…”
Section: Aea Hydrolase Faah Inhibitors In Treatment For Anxietymentioning
confidence: 97%
“…As such, humans who possess the rare variant of the C385A FAAH SNP represent a population who have elevations in AEA signaling. Consistent with what has been found in the rodent literature, humans bearing the C385A FAAH SNP exhibit lower levels of trait anxiety, blunted reactivity of the amygdala in response to threat, increased functional and structural connectivity between the ventromedial prefrontal cortex and the amygdala and enhanced fear extinction (Demers, Drabant Conley, Bogdan, & Hariri, 2016 ; Dincheva et al, 2015 ; Gärtner et al, 2019 ; Gee et al, 2016 ; Green et al, 2021 ; Gunduz-Cinar et al, 2013 ; Hariri et al, 2009 ; Sisk et al, 2022 ; Zabik et al, 2022 ). Individuals with PTSD who possess this FAAH SNP also exhibit reduced symptoms of arousal and blunted stress-induced anxiety (Spagnolo et al, 2016 ), as well as enhanced treatment responses to virtual reality-assisted psychotherapy with D-cycloserine augmentation, particularly in those who have comorbid major depression and PTSD (Difede et al, 2022 ).…”
Section: Stress-related Psychiatric Disordersmentioning
confidence: 99%